The Archaeological Distribution of the Cuneiform Corpus: A Provisional Quantitative and Geospatial Survey - Rattenborg, Rune (Altorientalische Forschungen, 2023)
The present study offers a first comprehensive, quantifiable overview of the geographical extent and scale of the cuneiform corpus. Though one of the oldest and longest-lived scripts in history, the sheer size of this corpus, being among the largest discrete bodies of written source material from the pre-modern world, is seldom properly appreciated. We review and evaluate past quantitative assessments of the corpus and current levels of catalogue digitisation and integration, pointing to gaps in general catalogues and principal issues relating to the quantification and interrogation of textual sources at the corpus-level. Combining a newly developed open access spatial index of c. 600 locations from across Europe, Asia, and Africa where cuneiform texts have been found with a quantitative survey of reported finds from scholarly literature, we then proceed to discuss the formation of the cuneiform corpus as an archaeological artefact. Aided by an extremely broad diachronic and diatopic outlook on a uniquely large body of written source material, this study offers an innovative and novel perspective on written corpora as archaeological artefacts.